Expert System To Diagnose Periodontal Disease Using Certainty Factor Method - Ferdynan Mashaq; Herlina Latipa Sari; Prahasti Prahasti (Penerbit Jurnal Indonesia, 2021)
This study aims to create an expert system application to diagnose periodontal disease in humans using the Certainty Factor Method. Periodontal is a dental disease that causes tooth loss due to inflammation from bacteria that results in progressive damage to the supporting tissues of the teeth. The problem that often occurs is the lack of knowledge and limited sources of information causing low public awareness of efforts to prevent and even treat dental and oral diseases. The MySQL database can accommodate patient information and data who consult with an expert system that can provide convenience for patients to consult about periodontal disease. From the results of the system program on the users, it was found that the average results of respondents' answers which reached 53% answered strongly agree, 26% answered agree, 14% answered less agree and only 7% of respondents answered disagreed. So from the results of data processing, it can be concluded that this system is feasible to use. Because more than half of the respondents agree that this system is suitable to use.